1999
DOI: 10.1093/ps/78.5.699
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microbial phytase on apparent ileal amino acid digestibility of feedstuffs for broilers

Abstract: The influence of microbial phytase on the ileal amino acid digestibilities in three cereals (corn, sorghum, and wheat), four oilseed meals (soybean meal, canola meal, cottonseed meal, and sunflower meal) and two cereal by-products (wheat middlings and rice polishings) was determined using 5-wk-old broilers. Supplementation of microbial phytase (1,200 FTU/kg) improved (P < 0.001 to 0.10) the digestibilities of protein and amino acids in all feedstuffs, but the magnitude of response varied depending on the feeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
145
0
18

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(178 citation statements)
references
References 9 publications
15
145
0
18
Order By: Relevance
“…Another possible outcome would be reduced substrate availability (Ca 2+ ) used in the formation of ternary protein-phytate complexes. The results of this study support previous findings that dietary Ca concentration influences the digestibility of N and amino acids (Ravindran et al 1999;Selle et al 2009). In the present study, the improvement of apparent digestibility of amino acids was broadly in keeping with the results of Cowieson et al (2006) who reported ingestion of fully phosphorylated phytate (IP 6 ) adversely affected the true digestibility coefficients of alanine, serine, aspartic acid and threonine to a greater extent than other amino acids.…”
Section: Discussionsupporting
confidence: 91%
“…Another possible outcome would be reduced substrate availability (Ca 2+ ) used in the formation of ternary protein-phytate complexes. The results of this study support previous findings that dietary Ca concentration influences the digestibility of N and amino acids (Ravindran et al 1999;Selle et al 2009). In the present study, the improvement of apparent digestibility of amino acids was broadly in keeping with the results of Cowieson et al (2006) who reported ingestion of fully phosphorylated phytate (IP 6 ) adversely affected the true digestibility coefficients of alanine, serine, aspartic acid and threonine to a greater extent than other amino acids.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, some researchers reported that microbial phytase had a beneficial effect on the utilization of nutrients other than phosphorus, such as amino acids (Yi et al, 1996;Namkung and Leeson, 1999;Ravindran et al, 1999Ravindran et al, , 2000. Furthermore, several studies showed that added phytase improved ileal amino acid digestibility in individual feed ingredients (Ravindran et al, 1999;Rutherfurd et al, 2002) and in complete diets (Yi et al, 1996;Namkung and Leeson, 1999;Ravindran et al, 2000).…”
mentioning
confidence: 99%
“…Furthermore, several studies showed that added phytase improved ileal amino acid digestibility in individual feed ingredients (Ravindran et al, 1999;Rutherfurd et al, 2002) and in complete diets (Yi et al, 1996;Namkung and Leeson, 1999;Ravindran et al, 2000). However, this topic remains still controversial because in some other experiments only marginal or even no effects were observed (Sebastian et al, 1997;Biehl and Baker, 1997;Zhang et al, 1999;Peter et al, 2000).…”
mentioning
confidence: 99%
“…Estes resultados confirmam o efeito benéfico da fitase microbiana sobre a hidrólise Tabela 1 -Composição das dietas experimentais (% matéria natural) do ácido fítico, incrementando a digestibilidade ileal de nutrientes nas dietas de frangos. As bases para estes achados estão se tornando evidentes e claramente relacionadas com a capacidade do ácido fítico em se ligar a proteínas, aminoácidos, amido e lipídios e da habilidade da enzima em liberar os nutrientes complexados à molécula, pela hidrólise do ácido fítico (RAVINDRAN et al,1999). A média dos valores de digestibilidade ileal da matéria seca e da energia bruta foram maiores (P<0,05) em rações com baixos níveis de Ca e P d , no entanto, para proteína bruta, os maiores valores foram observados nas dietas com baixo nível de Ca e P d (P>0,05).…”
Section: Experimentounclassified
“…No entanto, alguns estudos demostraram melhoras similares às encontradas neste trabalho (MARSMANN et al, 1997;RAVINDRAN et al, 1999;ZANELLA et al, 1999;e NAMKUNG e LEESON, 1999).…”
Section: Experimentounclassified